Paper Strength Development with Beating and Polyamideamine-epichlorohydrin (PAE) - Maria Ulfa; Bambang Setiaji; Wega Trisunaryanti; Triyono Triyono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
Thecharacter of coir handsheets prepared with beating and addition of polyamideamine-epichlorohydrin (PAE) was investigated. Pulp coir from soda-anthraquinone pulping was used as raw material for manufacture of coir handsheets. Physical and mechanical properties obtained with different beating level and PAE dosage were measured. The addition of PAE 10% w/w and beating on pulp stock of 3000 rev increased grammage and density at 1.9 and 15.8%, respectively. Instead it decreased thickness by 15.8%. Addition PAE dosage of 10% w/w at 10000 rev improved the density, but decreased the porosity and Cobb60 at 5.8; 10.2; and 19 %, respectively. The highest dry and wet tensile were obtained at 20 % w/w of PAE. Combination of beating and addition of PAE on pulp stock formed wet-strength handsheets with range between 28.0 to 34.2%.